Nanobodies: New ammunition to battle viruses - Vanlandschoot, P.; Stortelers, C.; Beirnaert, E.; Ibañez, L. I.; Schepens, B.; Depla, E.; Saelens, X.
In 1989, a new type of antibody was identified, first in the sera of dromedaries and later also in all other species of the Camelidae family. These antibodies do not contain a light chain and also lack the first constant heavy domain. Today it is still unclear what the evolutionary advantage of such heavy chain-only antibodies could be. In sharp contrast, the broad applicability of the isolated variable antigen-binding domains (VHH)was rapidly recognized, especially for the development of therapeutic proteins, called Nanobodies_. Here we summarize first some of the unique characteristics and features of VHHs. These will next be described in the context of different experimental therapeutic applications of Nanobodies against different viruses: HIV, Hepatitis B virus, influenza virus, Respiratory Syncytial virus, Rabies virus, FMDV, Poliovirus, Rotavirus, and PERVs. Next, the diagnostic application of VHHs (Vaccinia virus, Marburg virus and plant Tulip virus X), as well as an industrial application (lytic lactococcal 936 phage)will be described. In addition, the described data show that monovalent Nanobodies can possess unique characteristics not observed with conventional antibodies. The straightforward formatting into bivalent, multivalent, and/or multispecific Nanobodies allowed tailoring molecules for potency and cross-reactivity against viral targets with high sequence diversity.
Keywords: NANOBODY; CAMELIDAE; HEAVY CHAIN-ONLY ANTIBODY; VHH; ANTIVIRAL